2018
DOI: 10.1186/s13578-018-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2 acts as a biomarker for GIST risk category and suppresses the viability and invasiveness of GIST cells

Abstract: Evaluating the risk category of gastrointestinal stromal tumors (GISTs) is crucial for predicting prognosis and choosing treatment strategies, and tumor metastasis usually represent poor prognosis. Tumor necrosis factor-alpha-induced protein 8-like 2 (TIPE2) is a novel described tumor suppressor. In the present study, TIPE2 expression was detected using a total of 96 human GIST specimens by immunohistochemistry. The effect of TIPE2 on proliferation and invasiveness of GIST cells and its related mechanisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…TIPE2 has been shown to exert an inhibitory effect on GIST cell proliferation and invasion by targeting Rac1 [22]. A study published in 2019 revealed that SNAI2 and CDH1 are associated with GIST metastasis.…”
Section: Other Relevant Mechanismsmentioning
confidence: 99%
“…TIPE2 has been shown to exert an inhibitory effect on GIST cell proliferation and invasion by targeting Rac1 [22]. A study published in 2019 revealed that SNAI2 and CDH1 are associated with GIST metastasis.…”
Section: Other Relevant Mechanismsmentioning
confidence: 99%
“…Overexpression of TIPE2 in tumor cells induced cell apoptosis and significantly inhibited Ras-induced tumorigenesis through binding to Ras-interacting domain of RGL and inhibiting the activation of Ral ( 9 ). In addition, TIPE2 inhibited invasiveness and tumor development via reducing MMP9 expression by targeting Rac1 in hepatocellular carcinoma (HCC) and gastrointestinal stromal tumor ( 11 , 12 ). TIPE2 also inhibited HCC metastasis through suppressing Erk1/2 and NF-κB activation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 TIPE is the founding member of the TIPE -family which also includes the TNFAIP8-like 1 (TIPE1), TNFAIP8-like 2 (TIPE2), and TNFAIP8-like 3 (TIPE3) proteins and plays important roles in the development and progression of cancers. [17][18][19][20][21][22][23] Overexpression of TIPE is frequently observed in malignant cells and is strongly linked to excessive proliferation, reduced apoptosis, enhanced invasion and metastasis. 24 Studies have shown that TIPE overexpression was correlated with cancer progression and poor prognosis in patients with non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%